Positive Cumulative Fluids Balance Related to Mortality Events in Sepsis Patients Treated at Intensive Care Unit, Dr. Mohammad Hoesin General Hospital Palembang - Zulkifli; Fredi Heru Irwanto; Legiran; Nadia Maharni (Journal of Anesthesiology and Clinical Research, 2021)
Introduction. Sepsis is a syndrome that describes physiological dysfunction, pathological, and biochemistry caused by infection. Fluid balance is an indicator that can monitor input and output. This study was aimed to evaluate the relationship between positive cumulative fluid balance and the mortality rate of sepsis patients treated in the intensive care unit. Method: This study design is a retrospective study. The inclusion criteria consist of patients diagnosed with sepsis written in the medical record, 18-65 years old, and patients admitted in intensive care unit dr Moh. Hoesin General Hospital. Data were analyzed using SPSS 22.0 with the normality of data distribution, independent sample t-test, Mann-Whitney analysis, chi-square, Fisher’s Exact to measure the relationship, and using Medcalc version 14 application to measure cut-off value, ROC curve AUC, cross-sectional point, sensitivity, and specificity. Result. The result showed that characteristic between age (p=0,491), gender (p=0,703) did not differ significantly between survived and non-survived patient. Length of stay (p=0,002), balance (p=0,000), and ward unit (p=0,014) has a significant different between survived and non survived patient. In chi square analysis, p value=0,000with odds ratio 7,083. Cut-off value of ROC curve is -97 mL with AUC 0,844, sensitivity 76,1% and specificity 79,3%. Conclusion. Cumulative positive balance patient in the sepsis patient correlates with increased mortality in a sepsis patient in Dr. Mohammad Hoesin General Hospital Palembang.